Energy Harvesting and Efficiency of Floating Solar Panels - Abd.Wahab, Abdul Hadi; Mustafa, Farahiyah (Progress in Engineering Application and Technology, 2024)
Floating solar panels are an innovative renewable energy technology designed to optimize energy generation by addressing the limitations of traditional ground-mounted solar installations. This project developed a prototype floating solar panel system with a high-density polyethene (HDPE) platform and photovoltaic (PV) panels. Key components include managing shading using a 775 DC motor by cutting creepers away from solar panels and running loads.. The system was evaluated under various environmental conditions, demonstrating effective thermal management, stable power output, and reliable operation. Floating PV systems showed improved cooling efficiency and consistent performance compared to ground-mounted systems, especially during peak sunlight hours.